THE RESEARCH ON THE INNOVATIVE POTENTIAL OF SMALL AND MEDIUM-SIZED ENTERPRISES UNDER THE FORMATION OF A NEW TECHNOLOGICAL STRUCTURE (BASED ON DATA OF EAST KAZAKHSTAN REGION) - Bayadilova B.M (Academic Journal of Physical and Chemical Sciences, 2019)
The article presents the current state of small and medium-sized businesses in the East Kazakhstan region of the Republic of Kazakhstan, in particular, the dynamics and structure of active innovatively developed small and medium-sized businesses, the main indicators characterizing the development of small businesses in the context of the formation of a new technological structure in the region. The innovative potential of enterprises of the East Kazakhstan region is also considered, that is, the degree of its readiness to perform the tasks of small and medium-sized businesses, ensuring the achievement of the set innovation goal, the structure of performance indicators of small and medium-sized businesses, as well as the degree of readiness to implement an innovative project innovation transformation and innovation programs.